INNOVATIVE PLATFORM OF THE PARADIGM OF ENERGY SAVING OF DEVELOPMENT: MODERN TRENDS AND IMPERATIVES OF REALIZATION IN UKRAINE - Klymchuk , M.M.; Yemelianova , O.M.; Ilina , T.A.; Klymchuk , S.A. (The actual problems of regional economy development, 2021)
A significant level of energy dependence and energy intensity of the building complex of Ukraine needs to develop an effective energy saving interdisciplinary concept development, which will enable to implement investment projects on construction platform energy efficiency. The concept is based on syncretism: «Environmental Economics», «Green Lease», «Urban economy», «Surveying», «Passive House». One of the newest tools of development proposed to use energy-efficient Buildings Industry Transportation Electricity Scenarios (BITES), based on a scenario analysis of changes in energy supply and demand real economy, as well as evaluating the emissions of carbon dioxide production. Given the current trends in energy efficiency in the construction industry, it is proposed to implement in practice the management of investment and construction projects, the concept of «energy-saving development» and define it as a system implementing a set of measures of economic, organizational, technical, technological, legal, environmental and social, aimed at reducing building energy costs based on the introduction of energy efficient technologies and management practices, as well as organizational sphere, optimization of business processes and interconnection of links within the production chain. The theoretical foundations of interdisciplinary concept of development of building energy saving sector, where defined parametric performance and functional characteristics that are the basis for developing a strategic mechanism for its implementation at all levels of the economic system in order to reduce energy dependence of our country. The results of the study can be implemented at all levels of the economic system, as the issue of improving energy efficiency is relevant. The developed interdisciplinary concept of energy-saving development of the construction complex takes into account the specifics of the development of the construction sector market and global trends, which are reflected in the latest concepts: «Environmental Economics», «Green Lease», «Urban economy», «Surveying», «Passive House».